Le droit pénal de l’environnement : une garantie d'impunité ? - Grandbois, Maryse (Criminologie, 1988)
The limits of pollution authorized by law are constantly being exceeded in Quebec and throughout Canada, as evidenced by acid rain, the disposal of dangerous refuse in nature and the uncontrolled use of pesticides. The criminal law on the environment exists, to be sure, but its application is highly relative. In principle, certain infractions under the Criminal Code can be used against polluters but the State rarely makes use of them. As to the statutory criminal law -the main subject of this article - the author notes that it suffers from a lack of clarity and precision. Complex and unorganized, it is characterized by a multitude of infractions and a disparity of sanctions. However, the fact is that the public administration very seldom resorts to the provisions of this law to have industrial activities conform to the laws and regulations. When it does do so, very often the courts hesitate to impose sanctions of a truly deterrent nature. In spite of all this, the fact is that the main obstacle to the criminal law on the environment is the lack of firm determination on the part of the legislators and public administrations to use severe measures against polluters. As long as this political will is lacking, notes the author, certain major industrials will continue to contaminate the environment with impunity.